Tailoring an online breastfeeding course for Southeast Asian paediatric trainees- A qualitative study of user experience from Malaysia and Thailand - Lee Y.K. (2023)
Background: This study explored the user experiences of paediatric postgraduate trainees in Malaysia and Thailand in using a 2 h and 15 min online module for breastfeeding developed for Southeast Asia, which was adapted from existing European online modules for European and German Continuing Medical Education (CME) credits. Methods: A qualitative study using focus group discussions (FGDs) was conducted with paediatric postgraduate trainees who used an online English-language breastfeeding module in two Thai universities (May 2020, done online) and two Malaysian universities (Sept- Nov 2019, in-person). FGDs explored module usability and utility. Sessions were transcribed verbatim and analysed thematically. The process of coding was done collaboratively by Thai and Malaysian researchers. Results: Twenty Six resident trainees participated (Thai, n = 13; Malaysian, n = 13). Ages ranged from 29–34 years old, with 21 females. Nineteen participants had never used online learning modules prior to this. Participants took between 1 to 5 sessions to complete the breastfeeding module. Four themes emerged from their experience. 1) The online learning module was more engaging and detailed than previous lectures, courses and/or books, but lacked hands-on training. 2) Using an online platform facilitated learning as eased navigation and resource searching, however, problems were encountered navigating the module on some devices. 3) Learners preferred less words and more graphics, as this helped them capture key messages. 4) Regionally tailored content elicited a mixed reaction from participants. Conclusions: Users found that the adapted module compared favourably with previous learning experiences. However, online learning modules lack hands-on training, and implementation should ideally incorporate a mix of both. Consideration of device diversity and preferences for how content was adapted for local settings are needed for tailoring.